Characterizing the lacrimal punctal region using anterior segment optical coherence tomography. (9th December 2015) - Timlin, Hannah M.; Keane, Pearse A.; Day, Alexander C.; Salam, Tahrina; Abdullah, Mohammed; Rose, Geoffrey E.; Ezra, Daniel G.
Abstract: Purpose: Abnormalities of lacrimal punctum size and morphology probably contribute to excess tearing, with significant effects on quality‐of‐life for affected individuals. Our current understanding of normal punctal morphology originates from ex vivo studies, which are unlikely to capture the true nature of the living punctum. This study used enhanced depth anterior segment optical coherence tomography (OCT) to give improved characterization and understanding of lacrimal punctal structure. Methods: Qualitative and quantitative assessments were performed on spectral domain OCT images collected prospectively from 40 lower puncta of 20 healthy volunteers. Results: The average external lower lid punctal diameter was 0.646 mm (SD 150  μ m) on OCT imaging, measured at the largest diameter, which was in parallel to the mucocutaneous junction. Fifty‐five per cent of puncta appeared closed, whilst the eyelids were open. Fluid menisci were visible within 73% of puncta. A postpunctal 'ampulla' was visible within three systems, one of which was imaged through the conjunctival surface. Ampullary dilatation occurred laterally, rather than at the medial wall. Conclusion: Optical coherence tomography provides quick and non‐invasive assessment of the lacrimal punctum and its neighbouring tissue layers. This assessment of punctal size and morphology has the potential for further investigation of punctal physiology, for aiding diagnosis, and for monitoring the results of treatment. The average external diameter of the punctal opening measured in this study is greater than that recorded in anatomical textbooks.